Pengaruh Komunikasi Interpersonal Penjual Umkm Terhadap Kepuasan Pelanggan Di Desa Kebak - Isrianto Islamudin; Romi Iriandi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
This study aims to analyze the influence of interpersonal communication between UMKM sellers on customer satisfaction in Kebak Village. Interpersonal communication is considered an important factor in determining the quality of the relationship between sellers and customers during transactions. This study used a quantitative, associative design to examine the relationship between interpersonal communication variables and customer satisfaction. Primary data were obtained by distributing questionnaires to 140 UMKM buyers in Kebak Village who were selected as respondents. The research instrument used a Likert scale to measure interpersonal communication indicators, including openness, empathy, positive attitude, support, and equality, as well as customer satisfaction indicators. Data analysis was performed using IBM SPSS Statistics 29, including normality and linearity tests and Spearman's rho correlation tests. The results showed that the data met the required statistical assumptions and there was a positive and significant relationship between sellers' interpersonal communication and customer satisfaction. This finding indicates that improving the quality of interpersonal communication is often followed by an increase in customer satisfaction. Effective interactions can create a sense of comfort, trust, and a positive experience during the transaction process. This study confirms that interpersonal communication is a strategic factor in improving service quality and strengthening relationships between UMKM and customers. The research implications underscore the importance of developing interpersonal communication competencies to increase customer satisfaction and the competitiveness of UMKM.